Effect of avocado/soybean unsaponifiables on periodontal repair in rats with arthritis and induced periodontitis - Tsurumaki, Jackeline do Nascimento [UNESP]; Paula, Luiz Guilherme Freitas de; Aquino, Sabrina Garcia de; Marcantonio, Elcio [UNESP]; Oliveira, Guilherme José Pimentel Lopes de; Marcantonio, Rosemary Adriana Chiérici [UNESP] (FapUNIFESP (SciELO), 2019)
OBJECTIVE: This study aimed to evaluate the effect of avocado/soybean unsaponifiables (ASU) on periodontal repair in rats with induced periodontitis and arthritis. METHODOLOGY: Forty-five rats were submitted to periodontitis induction by insertion of ligatures into the upper second molars, maintained for 15 days. These animals were randomly allocated to 3 groups according to the presence of induced arthritis (ART) and the application of the ASU: Control (CTR) group-healthy animals, where saline solution was administered; ART-animals with induced arthritis, where saline solution was administered; ART/ASU-animals with induced arthritis, where ASU (0.6 mg/ kg) was administered. The drugs were administered daily by gavage and the animals were euthanized after 7, 15 and 30 days of the ligature removal. Bone resorption, inflammatory infiltrate composition and marker proteins expression of the differentiation and formation of osteoclasts (RANKL and TRAP) were assessed. RESULTS: The ART/ASU group presented higher bone volume than the ART group at 7 and 30 days after the ligature removal. Furthermore, the ART group presented higher quantity of inflammatory cells and expression of TRAP and RANKL than the other groups. CONCLUSION: ASU administration improves the repair of periodontal tissues in an experimental periodontitis model in rats with induced arthritis.